Pre-performance rituals and anxiety among young Polish and Ukrainian football players - Basiaga-Pasternak, J. (Baltic Journal of Health and Physical Activity, 2019)
Rituals and superstitions are also present in sport, as a part of sport competition. Rituals, usually conceived as superstitions, have survived among people. They comprise magical thinking, belief in specific sayings, ritualized behavior, specific interpretation of events. They are practiced to reduce anxiety. The purpose of the study was to identify the most common pre-competitive superstition rituals among Polish and Ukrainian football players and establish the relationship between superstitions and anxiety. Material and Methods: Participants were 100 Polish and 50 Ukrainian adolescent football players. The Rituals in Sport and the Sport Anxiety Scale were used. Results: The results have shown that most common rituals used by football players are superstitions and elements of pre-performance routine. Athletes used religious and personal rituals to increase their self-confidence. Some respondents exhibit ritualized behavior which might be considered as an element of pre-performance routine. Conclusions: The study found that as the level of pre-performance anxiety increased, the level of rituals also increased.